Self- Declaration: Justifikasi Dusun Nogosari atas Diri sebagai Desa Pancasila - Permatasari, Rr. Yudiswara Ayu; Elasalama, Nadia; Alfariz, Fitri (Journal of Civic Education, 2024)
This research provides philosophical arguments through logical and axiological analysis of the validity of the Nogosari Village that claim as Pancasila Village and provides an evaluation of the Desa Pancasila concept offered by the Government. This concept given by Agency for the Development of Pancasila Ideology (BPIP) and the Ministry of Villages, Underdeveloped Regions and Transmigration (Kemendes PDTT). The research method uses philosophical research on actual problems by collecting data using observation and interviews with residents of Nogosari Village in Bantul. This reseacrh were carried out during community service by Faculty of Philosophy, Gadjah Mada University. The results show the insufficient definition of Desa Pancasila which resulted in Nogosari Village being excluded from Desa Pancasila by BPIP and the Kemendes PDTT. Thus, there is vagueness in the concept of Pancasila Village formulated by the Government. This research also proposes suggestions for a re-examination of the Desa Pancasila concept and justification for the Desa Pancasila in Nogosari Village by the Government.